The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1516-635x2009000300007
|View full text |Cite
|
Sign up to set email alerts
|

Internal quality of conventional and omega-3-enriched commercial eggs stored under different temperatures

Abstract: The internal quality of conventional and ω-3 enriched commercial eggs stored at different temperatures was evaluated. Eggs derived from Isa Brown layers fed two different diets. In Group 1, 432 hens were fed throughout their productive life with a diet based on corn and soybean meal (production of conventional eggs). In Group 2, starting at 22 weeks of age, other 432 hens were fed a diet containing 1.5% of marine algae substrate and 1.8% of fish oil (production of ω-3 enriched eggs). The following pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Egg types presented similar change (p > 0.05) of the albumen pH both in refrigeration and under room temperature, which is consistent with the result of Pappas, A.C. [23,44] who observed that the albumen pH increased as the time extended irrespective of the egg types.…”
Section: Comparison Of Quality Changes Of N-3 Pufas Enriched and Convsupporting
confidence: 89%
See 2 more Smart Citations
“…Egg types presented similar change (p > 0.05) of the albumen pH both in refrigeration and under room temperature, which is consistent with the result of Pappas, A.C. [23,44] who observed that the albumen pH increased as the time extended irrespective of the egg types.…”
Section: Comparison Of Quality Changes Of N-3 Pufas Enriched and Convsupporting
confidence: 89%
“…Take n-3 PUFAs enriched eggs as an example, Albumen pH went up to 9.36 from 8.40, 11.4% increase after 30 days storage in refrigeration, while those under room temperature, it just took 18 days for albumen pH to increase 12.1%, from 8.4 to 9.42. It is believed that the escape of CO2 and water leads to the rise of albumen pH during storage [23,36]. …”
Section: Changes Of Albumen Phmentioning
confidence: 99%
See 1 more Smart Citation
“…The output of H 2 O and CO 2 from the egg contents to the external environment promotes an increase in the pH of the albumen by unbalancing the carbonic acid (H 2 CO 3 ) buffering system (Cedro et al, 2009). Therefore, the tested coatings may have contributed to the conservation of the buffer system by reducing the release of H 2 O and CO 2 from the interior of the eggs.…”
Section: Albumen and Yolk Phmentioning
confidence: 99%
“…It was shown that Haugh unit (Al-Saffar and Rose, 2002) and albumen height (El-Tarabany et al, 2016) were not influenced by stress. Likewise, dietary flaxseed oil and sunflower oil supplementations were reported to have no impact on the Haugh unit (Cherian et al, 2007;Midilli et al, 2009) and albumen height (Cedro et al, 2009). Egg yolk color is a crucial intrinsic egg quality parameter that determines consumer preferences.…”
Section: Discussionmentioning
confidence: 99%